2014
DOI: 10.1080/13554794.2014.973883
|View full text |Cite
|
Sign up to set email alerts
|

Smile without euphoria induced by deep brain stimulation: a case report

Abstract: Poststroke central pain (PSCP) can be a debilitating medication-refractory disorder. We report a single case where right unilateral ventral capsule/ventral striatum (VC/VS) deep brain stimulation was used to treat PSCP and inadvertently induced a smile without euphoria. The patient was a 69 year-old woman who had a stroke with resultant dysesthesia and allodynia in her left hemibody and also a painful left hemibody dystonia. In her case, VC/VS stimulation induced a smile phenomenon, but without a euphoric sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Recently, neuropsychiatric DBS approaches have been applied to address the affective components of pain in pain disorders. The DBS targets included limbic structures, the anterior cingulate cortex (ACC; Boccard et al, 2014a , b ), and the ventral capsule/ventral striatum (VC/VS; Machado et al, 2013 ; Morishita et al, 2015a ). The ACC stimulation was applied based on the experience of anterior cingulotomy for intractable pain and obsessive-compulsive disorder (OCD; Brotis et al, 2009 ).…”
Section: Invasive Brain Stimulation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, neuropsychiatric DBS approaches have been applied to address the affective components of pain in pain disorders. The DBS targets included limbic structures, the anterior cingulate cortex (ACC; Boccard et al, 2014a , b ), and the ventral capsule/ventral striatum (VC/VS; Machado et al, 2013 ; Morishita et al, 2015a ). The ACC stimulation was applied based on the experience of anterior cingulotomy for intractable pain and obsessive-compulsive disorder (OCD; Brotis et al, 2009 ).…”
Section: Invasive Brain Stimulation Proceduresmentioning
confidence: 99%
“…Boccard et al reported favorable outcomes in the pain levels and QOL of 11 patients who had follow-up evaluations after bilateral ACC DBS (Boccard et al, 2014a ). However, Morishita et al ( 2015a ) reported an unsuccessful case of unilateral VC/VS stimulation. Currently, a bilateral VC/VS DBS study is underway (clinicalTrial.gov Identifier: NCT01072656).…”
Section: Invasive Brain Stimulation Proceduresmentioning
confidence: 99%
“…They did note, however, that patients experienced improvement in the affective component of their pain. An additional patient implanted with VC/VS and ventral oralis electrodes did not achieve satisfactory pain relief [72]. Although stimulation of the VC/VS may be a prospective treatment option, there is not enough data to warrant its current use in clinical practice.…”
Section: Methodsmentioning
confidence: 99%